Various Antibody Clones of Napsin A, Thyroid Transcription Factor 1, and p40 and Comparisons With Cytokeratin 5 and p63 in Histopathologic Diagnostics of Non–Small Cell Lung Carcinoma. Issue 9 (October 2016) - Tran, Lena; Mattsson, Johanna S.M.; Nodin, Björn; Jönsson, Per; Planck, Maria; Jirström, Karin; Botling, Johan; Micke, Patrick; Brunnström, Hans
Abstract : Histopathologic classification of cancer in the lung is important for choice of treatment. Cytokeratin 5 (CK5), p63, and p40 are commonly used immunohistochemical markers for squamous cell carcinoma, and napsin A (NAPA) and thyroid transcription factor 1 (TTF-1) are markers for adenocarcinoma of the lung. The aim of the present study was to evaluate these 5 markers and to compare different commercially available antibody clones in lung cancer. Tissue microarrays including 557 cases of surgically treated primary tumors and 73 matched metastases of non–small cell lung carcinoma were stained with CK5, p63, p40 (monoclonal and polyclonal), NAPA (5 different clones/protocols), and TTF-1 (2 different clones). The sensitivity and specificity to separate squamous cell carcinomas from non–small cell carcinomas of nonsquamous type were 95% and 97%, respectively, for CK5, 95% and 87% for p63, 94% and 96% for p40, 75% to 79% and 96% to 98% for the NAPA clones/protocols and 80% to 85% and 95% to 97% for the TTF-1 clones. A combination of NAPA and TTF-1 resulted in a higher sensitivity (85% to 88%), whereas combining CK5 and p40 did not increase the diagnostic performance. The sensitivity was generally lower in evaluation of lung cancer metastases. The κ-values for comparison of staining results between monoclonal and polyclonal p40 and between the 5 NAPA clones/protocols were 0.97 to 1.0, whereas the corresponding figure for the 2 TTF-1 clones was 0.91 to 0.93. Conclusively, CK5 and p40 are good diagnostic markers for squamous cell carcinoma and superior to p63. In addition, it may be useful to combine NAPA and TTF-1 for increased sensitivity in lung cancer diagnostics. There is no substantial difference between monoclonal and polyclonal p40 and between different NAPA clones, whereas there is a difference between the TTF-1 clones 8G7G3/1 and SPT24.